KINERJA APARATUR SIPIL NEGARA DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SULAWESI TENGAH - Kapile, Joice Fransiska; Mangasing, Nasir; Aksan, Sitti Chaeriah (Katalogis, 2021)
The research aims to analyze the performance of state civil apparatus in the Secretariat of Regional People's Representatives of Central Sulawesi Province. The research applied a qualitative method. The research setting was at the Secretariat of Regional People's Representatives of Central Sulawesi Province. The informants were 5 people selected using Purposive Sampling technique. The data were gathered through observation, interview, and documentation. In this case, the researcher used Miles and Huberman analysis approach. The research findings show that the performance of state civil apparatus in the Secretariat of Regional People's Representatives of Central Sulawesi Province with indicators such as 1. Productivity shows that efficiency and effectiveness have not run maximally. 2. Service Quality shows that the satisfaction on the service given has been fulfilled. 3. Responsiveness shows that the ability of the apparatus of Regional People's Representatives of Central Sulawesi Province to recognize the needs of service receiver, arrange agenda and service priority and develop public service programs are suitable with communities needs and aspiration have been run well. 4. Responsibility shows that the programs have already been properly as the right administration principles or adjust to organization policy. 5. Accountability shows thatÂ state civil apparatus in the Secretariat of Regional People's Representatives of Central Sulawesi Province obey to the political officials appointed by the people that marked by the accountability report.